Ignoring the elephant in the room? Assessing the impact of the European Union on the Development Assistance Committee's role in international development. (30th January 2018) - Verschaeve, Joren; Orbie, Jan
Abstract: This article studies the impact of the European Union (EU) on the Development Assistance Committee (DAC) of the Organisation for Economic Co‐operation and Development (OECD). While the literature thus far has focused on the external challenges for the DAC's role in international development, this study argues that the EU should be taken into account as well. By focusing on the cases of policy coherence for development and the concessionality of official development assistance (ODA) loans, we show that the EU poses a structural challenge for the DAC's role in international development given the strong overlap in membership between both institutions and the Union's changing nature as a development actor.